Genome-wide identification and analysis of arabidopsis sodium proton antiporter (NHX) and human sodium proton exchanger (NHE) homologs in sorghum bicolor - Kumari, P.H.; Kumar, S.A.; Ramesh, K.; Reddy, P.S.; Nagaraju, M.; Prakash, A.B.; Shah, T.; Henderson, A.; Srivastava, R.K.; Rajasheker, G.; Chitikineni, A.; Varshney, Rajeev K.; et al. (MDPI, 2018)
Na+ transporters play an important role during salt stress and development. The present study is aimed at genome-wide identification, in silico analysis of sodium-proton antiporter (NHX) and sodium-proton exchanger (NHE)-type transporters in Sorghum bicolor and their expression patterns under varied abiotic stress conditions. In Sorghum, seven NHX and nine NHE homologs were identified. Amiloride (a known inhibitor of Na+/H+ exchanger activity) binding motif was noticed in both types of the transporters. Chromosome 2 was found to be a hotspot region with five sodium transporters. Phylogenetic analysis inferred six ortholog and three paralog groups. To gain an insight into functional divergence of SbNHX/NHE transporters, real-time gene expression was performed under salt, drought, heat, and cold stresses in embryo, root, stem, and leaf tissues. Expression patterns revealed that both SbNHXs and SbNHEs are responsive either to single or multiple abiotic stresses. The predicted protein–protein interaction networks revealed that only SbNHX7 is involved in the calcineurin B-like proteins (CBL)- CBL interacting protein kinases (CIPK) pathway. The study provides insights into the functional divergence of SbNHX/NHE transporter genes with tissue specific expressions in Sorghum under different abiotic stress conditions.